2014
DOI: 10.1186/1475-2840-13-76
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of circulating adipokines and hsCRP association with cardiovascular disease risk factors and metabolic syndrome in Arabs

Abstract: BackgroundCardiovascular diseases (CVD) are a leading cause of death worldwide including the Middle East. This is caused in part by the dysregulation of adipose tissue leading to increased production of pro-inflammatory adipokines and reduction in cardio-protective adipokines such as adiponectin. Ethnicity has been recognized as a major factor in the association between CVD risk factors and the different circulating adipokines. In this study, for the first time, the relationship between traditional cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1
13

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 58 publications
1
59
1
13
Order By: Relevance
“…Triglycerides deposition in the adipocytes leads macrophageal activation and proinflammatory cytokines overproduction, as well as adipocytokines disregulation [7]. Leptin, PAI-1 and hsCRP showed significant positive association with increased MetS components (P-trend <0.05), while adiponectin was negatively associated with increased MetS components (P-trend <0.0001) [8]. As triggers of inflammation in adipose tissue can be adipocytes hypertrophy, local hypoxia, some of microorganisms such as Cytomegalovirus (CMV), H. pylori, C. Pneumoniae [9].…”
mentioning
confidence: 99%
“…Triglycerides deposition in the adipocytes leads macrophageal activation and proinflammatory cytokines overproduction, as well as adipocytokines disregulation [7]. Leptin, PAI-1 and hsCRP showed significant positive association with increased MetS components (P-trend <0.05), while adiponectin was negatively associated with increased MetS components (P-trend <0.0001) [8]. As triggers of inflammation in adipose tissue can be adipocytes hypertrophy, local hypoxia, some of microorganisms such as Cytomegalovirus (CMV), H. pylori, C. Pneumoniae [9].…”
mentioning
confidence: 99%
“…In addition, increased values of this marker have been associated with type 2 diabetes more than with other types in the context of the immunologic profiling of diabetic patients. While adiposity markers correlated positively with hsCRP, they also correlated negatively with adiponectin as an antiinflammatory, protective marker [19][20].…”
Section: Inflammation Assessmentmentioning
confidence: 93%
“…Although hyperuricemia is recognized as a risk factor for obesity, diabetes and MS, the precise physiological mechanisms by which uric acid contribute to these diseases state remain unclear 39 . Inflammation plays an important role in the pathogenesis of MS, hs-CRP has been found to be associated with MS 40 . Our study showed that the concentrations of hs-CRP were higher in subjects with MS than those without MS.…”
Section: Discussionmentioning
confidence: 99%